Originally Posted by

**calcbeg** Hi

The goal is to find the average value of the function h (t) = 1/(e^2t) over the interval (0,1)

So havg (1-0) = S a=0; b=1 e^-2t dt

So I am assuming I should do some substitution

let u = e^-2t then du =-2e^-2t dt so du/-2 = e^-2t dt

Then havg = S a=0;b=1 du/-2 = -1/2 S du = -1/2 (u) a=0;b=1

So then -1/2 (e^-2t) a=0;b=1

= -1/2 (e^-2 - e^0) **So far, so good**

= -1/(2e) + 1 **you simplified incorrectly**

Did I do this correctly???

Thanks

Calculus beginner - who no longer likes the letter e